Тестовое диагностирование одномерных однородных структур - Дербунович, Леонид Викторович; Бережная, М. А.; Королева, Я. Ю.; Рыжикова, М. Г. (НТУ "ХПИ", 2008)
Пропонується процедура синтезу перевіряючих тестів для виявлення класу функціональних несправностей в одномірних однорідних мережах (ОМ) по автоматним моделям осередка ОМ і знаходженню в них фундаментальних циклів. Також отримана оцінка трудомісткості процедури синтезу.

The test method of one-dimensional iterative logic arrays (ILAs), composed of identical cells, are considered. The fault model assumed is that faults in single cell can change a cell behavior in any arbitrary way. The method is based on finding fundamental circles in automaton model of ILA cell. The complexity of the test procedure is derived.
Keywords: дискретные устройства; однородная система; автоматная модель; модели неисправностей; алгоритм синтеза тестов; тестовый граф